ЛИЧНОСТНЫЕ ОСОБЕННОСТИ ПОТЕНЦИАЛЬНОЙ ЖЕРТВЫ ВЕРБОВЩИКА - Саида Арифханова; Султанова Лилия (World Science, 2018)
The processes of globalization, as we know create the migration flows, which involve the population of many countries. It leads to complicating of the social structural ties of specific communities and the world community as a whole. This can also be caused by tension in interethnic relations, which is accompanied by interethnic conflicts, and under these conditions, all sorts of opposition groups can be formed, including extremist ones.